2010
DOI: 10.1017/s0031182009992034
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream form trypanosome plasma membrane proteins: antigenic variation and invariant antigens

Abstract: Trypanosoma brucei is exposed to the adaptive immune system and complement in the blood of its mammalian hosts. The aim of this review is to analyse the role and regulation of the proteins present on the external face of the plasma membrane in the long-term persistence of an infection and transmission. In particular, the following are addressed: (1) antigenic variation of the variant surface glycoprotein (VSG), (2) the formation of an effective VSG barrier shielding invariant surface proteins, and (3) the rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 90 publications
1
56
0
1
Order By: Relevance
“…Indeed, to evade population clearance despite constant exposure to the host adaptive immune system, they have evolved a unique surface. This includes a layer of the variant surface glycoprotein (VSG) that coats the entire cell surface providing protection to other proteins 8. Within this coat operate important nutrient receptors and surface proteins with a role in avoiding the toxic effects of innate immune factors 9…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, to evade population clearance despite constant exposure to the host adaptive immune system, they have evolved a unique surface. This includes a layer of the variant surface glycoprotein (VSG) that coats the entire cell surface providing protection to other proteins 8. Within this coat operate important nutrient receptors and surface proteins with a role in avoiding the toxic effects of innate immune factors 9…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal domain is classified into three types, A, B and C (Carrington et al, 1991), although type C has been proposed to be classified as type A (Marcello and Barry, 2007). Despite their high primary sequence heterogeneity, all N-terminal domains fold with a similar tertiary structure, necessary to form the densely packed protective VSG coat, which exposes only a limited subset of immunogenic epitopes (Freymann et al, 1984;Blum et al, 1993;Chattopadhyay et al, 2005;Schwede and Carrington, 2010;Schwede et al, 2011). There are six types of C-terminal domains; types 2, 4 and 5 are single domains, while types 1, 3 and 6 are di-domains (Carrington et al, 1991;Marcello and Barry, 2007;Schwede and Carrington, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high primary sequence heterogeneity, all N-terminal domains fold with a similar tertiary structure, necessary to form the densely packed protective VSG coat, which exposes only a limited subset of immunogenic epitopes (Freymann et al, 1984;Blum et al, 1993;Chattopadhyay et al, 2005;Schwede and Carrington, 2010;Schwede et al, 2011). There are six types of C-terminal domains; types 2, 4 and 5 are single domains, while types 1, 3 and 6 are di-domains (Carrington et al, 1991;Marcello and Barry, 2007;Schwede and Carrington, 2010). The type 2 domain of MITat 1.2 and the type 1 domain of ILTat 1.24 share the same tertiary structure, arguing for conservation of the tertiary structure of both N-and C-terminal domains (Schwede and Carrington, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. brucei has two life cycle stages that are amenable to biochemical and biological studies: a procyclic form (PCF) found in the midgut of the tsetse fly and a pathogenic bloodstream form (BSF) in the mammalian host. Each has a glycoprotein coat composed of a stage-specific major surface glycoprotein: procyclins in the PCF stage (7) and variant surface glycoproteins (VSGs) in the BSF stage (8). Both VSGs and procyclins play pivotal roles in pathogenesis, VSG as the lynchpin of antigenic variation in the mammalian bloodstream (9) and procyclin as a critical component facilitating colonization in the tsetse midgut (10).…”
mentioning
confidence: 99%